Optimizing Competitiveness and Sustainability of Agribusiness SMEs through a Circular Economy Business Model - Ariyanti, Riska; Taryana, Asep (Newinera Publisher, 2024)
This study aims to optimize the competitiveness and sustainability of agribusiness SMEs in Indonesia through the application of the circular economy business model, using the design thinking approach, which includes the stages of empathize, define, ideate, and prototype. In light of increasing consumer awareness regarding sustainability, SMEs need to adapt in order to remain competitive. The circular economy offers solutions by utilizing waste as raw materials and extending product life cycles. This research is based on a literature review, direct discussions, and insights from a seminar presented by agribusiness owners, namely Mitra Tani Farm and Sangreat Natural Indonesia, to provide a deeper understanding of the application of the circular economy in the field. The findings indicate that circular economy-based strategies can improve operational efficiency and business resilience, while also providing positive environmental sustainability impacts, as demonstrated through case studies at Mitra Tani Farm and Sangreat Natural Indonesia. The prototype phase of this study outlines managerial implications that can be applied by agribusiness SMEs to enhance business sustainability. This article offers practical guidance for SMEs to achieve long-term sustainability while meeting market demands for responsible business practices.